Osteoporosis: Current Concepts - Akkawi, Ibrahim; Zmerly, Hassan (Joints, 2018)
Osteoporosis is a worldwide disease characterized by reduction of bone mass and alteration of bone architecture resulting in increased bone fragility and increased fracture risk. Causes of osteoporosis include increasing age, female sex, postmenopausal status, hypogonadism or premature ovarian failure, low body mass index, ethnic background, rheumatoid arthritis, low bone mineral density (BMD), vitamin D deficiency, low calcium intake, hyperkyphosis, current smoking, alcohol abuse, immobilization, and long-term use of certain medications. The diagnosis of osteoporosis is established by measurement of BMD of the hip and spine using dual energy X-ray absorptiometry. According to the World Health Organization criteria, osteoporosis is defined as a BMD that lies 2.5 standard deviation or more below the average value for young healthy women. Bone turnover biomarker detection may be useful in monitoring osteoporosis treatment and assessing fracture risk but not for diagnosis of osteoporosis. Management of osteoporosis consists of nonpharmacological interventions, which are recommended for all subjects, and pharmacological therapy in all postmenopausal women who have had an osteoporotic fracture or have BMD values consistent with osteoporosis.
Keywords: osteoporosis; DEXA; bone mineral density; anabolic agents; antiresorptive agents